Stress in High School Students: A Descriptive Study - Guadalupe Acosta-Gómez María; María De la Roca-Chiapas José; Zavala-Bervena Alicia; Eugenio Rivera Cisneros Antonio; Reyes Pérez Verónica; Da Silva Rodrigues Charles; Novack Keneth (Journal of Cognitive Behavioral Therapy, 2018)
School is a competitive place where people have many duties and responsibilities. This requires coping abilities to manage academic stress efficiently. Objectives a) Determine the general level of stress among high school students; b) identify the students’ main sources of stress; c) identify the students’ main responses to stress; d) determine if students have protections against or risk factors for stress. Materials & Method The stress levels and the main responses to stress of 335 high school students, aged 15–19 years, were surveyed using Nowack’s Stress Profile. Results and Discussion Most of the students reported normal (54%) or lower (39%) stress levels, but women reported significantly higher stress levels than men (p < 0.05). The main sources of stress were examinations, choosing a career path, and family troubles. The students’ main responses to stress were listening to music, talking with someone about the problem, and exercise.
Keywords: Stress